Przedsiębiorcy odpowiedzialni społecznie wobec reżimów totalitarnych i autorytarnych - Czechowski, Norbert (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Increasingly, there are voices of dissatisfaction in the public opinion towards the actions of entrepreneurs who indirectly support authoritarian or totalitarian authorities. The aim of this article is to find an answer to the question whether a socially responsible entrepreneur, obliged to respect and protect human freedoms and rights, can undertake actions supporting totalitarian and authoritarian regimes. When looking for answers, I will refer to business ethics, the concept of corporate social responsibility, soft law, as well as to normative obligations under national law.
Keywords: społeczna odpowiedzialność biznesu; przedsiębiorcy; prawa człowieka; totalitaryzm; autorytaryzm